Energy Retrofit Strategies in the Building Sector. - Dall’O’, Giuliano (Springer, 2020)
In the energy-environmental balance of a city, the building sector uses on average 40% of the energy taken from fossil fuel sources, thereby significantly contributing to air pollution and the emission of greenhouse gases. Green planning strategies must therefore carefully consider this sector, promoting energy retrofit actions that can contain environmental impacts. The energy and environmental redevelopment of buildings must not only be considered an emergency but also an interesting opportunity for growth in the construction market; however, some critical issues, not only of a technical but also economic and social nature, must be assessed. This chapter, focusing on the issue of energy and environmental redevelopment of buildings in cities and communities, on the territorial scale, aims to provide green planners with useful tools to approach their strategies in a pragmatic manner.
Keywords: Bebauung; Gebäude; Energetische Gebäudesanierung; Wärmedämmung; Nachrüstung; Außendämmung; Fallbeispiel; Energiesprong